Spatial and temporal patterns of economic segregation in Sweden's metropolitan areas: A mobility approach. (June 2018) - Östh, John; Shuttleworth, Ian; Niedomysl, Thomas
The statistical resources at hand for segregation research are usually almost exclusively confined to annual or decennial records where the only available spatial information is the individual's place of residence. This coarse temporal periodicity and spatial resolution provides a very limited account of people's diurnal lives. Incorporating mobility and temporal dimensions in segregation analysis is advocated within a growing body of research but there has rarely been sufficient data to make this possible. In this paper, we employ a fine-grained mobile phone dataset outlining the daily mobility of a substantial sample of the residents in Sweden's metropolitan areas. Combining spatial trajectory data with detailed socio-economic residential statistics, we are able to study how everyday spatial mobility in cities shapes the segregation experiences of people and changes the segregation levels of places. Results indicate that while mobility alleviates segregation for some individuals, the population of a large number of areas remain highly segregated even when daily mobility is taken into account. Individuals residing or spending time in central urban areas are more exposed to individuals from other areas because of daily moves to these central places. Daytime movement to central areas also reduces segregation significantly for people from places remote from city centres but with high average levels of mobility whilst daytime segregation levels remain close to their original night-time levels in low-mobility areas in the outskirts of the cities.